2019
DOI: 10.1007/s10681-019-2482-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heterosis for yield-related traits for single cross and three-way cross hybrids of oilseed rape (Brassica napus L.)

Abstract: Rapeseed breeding programs are focused mainly on improving plant potential and seed yield. One of the ways to improve seed yield in oilseed rape is heterosis, which is hybrid vigor that results in a greater biomass, increased seed yield, and faster development. The purpose of this study was to estimate yield-related trait heterosis for single cross and three-way cross hybrids of winter oilseed rape (Brassica napus L.). A population of 60 doubled-haploid (DH) lines and two generations of hybrids were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…There have been previous studies, which clearly demonstrate the trait specific nature of heterosis [25,56,57]. In B. napus and soybean, positive heterosis was seen for yield related traits (1000 seed weight and seed yield) but not for plant height [56,57]. van Hulten et al [58] reported that the genetic mechanisms underlying heterosis were highly trait specific and were largely dependent on the genetic background.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…There have been previous studies, which clearly demonstrate the trait specific nature of heterosis [25,56,57]. In B. napus and soybean, positive heterosis was seen for yield related traits (1000 seed weight and seed yield) but not for plant height [56,57]. van Hulten et al [58] reported that the genetic mechanisms underlying heterosis were highly trait specific and were largely dependent on the genetic background.…”
Section: Plos Onementioning
confidence: 97%
“…The highest value from the population for heterosis for plant height was 36% and 58% at the F 2 and sub selected F 3 generation respectively (Table 1). There have been previous studies, which clearly demonstrate the trait specific nature of heterosis [25,56,57]. In B. napus and soybean, positive heterosis was seen for yield related traits (1000 seed weight and seed yield) but not for plant height [56,57].…”
Section: Plos Onementioning
confidence: 98%
“…The following model was used to estimate general and specific combining ability effects of the ij th observations. [18] for some traits in Brassica napus.…”
Section: Discussionmentioning
confidence: 99%
“…Lint yield and fiber quality is strongly regulated by heterosis. In breeding programs, cytoplasmic male sterile (CMS) lines greatly accelerated the exploitation of heterosis in crops, such as rice (Song et al, 2021), rape (Wolko et al, 2019), wheat (Gupta et al, 2019). Since the discovery of first CMS gene T-urf13 in maize (Levings, 1976), molecular mechanisms of many CMS genes have been improved (Dewey et al, 1987;Moneger F, 1994;Song & Hedgcoth, 1994;H et al, 1995).…”
Section: Introductionmentioning
confidence: 99%